Respuestas

2012-05-09T00:54:28+02:00

x-1 = 2 ( y + 6 )

Despejamos x

x = 2 ( y + 6 ) +1

Reemplazamos aca

x + 6 = 3 ( 1 - 2y )

2 ( y + 6 ) +1 + 6 = 3 ( 1 - 2y )

2y + 12 + 1 + 6 = 3 - 6y

8y = 16

y = 2

 

Reemplazamos en cualquiera para sacar el valor de x

x-1 = 2 ( y + 6 )

x - 1 = 2 (8)

x = 17

 

ESPERO TE SIRVA

SALUDOS 

2012-05-09T01:02:51+02:00

x-1 = 2 ( y + 6 )

Despejamos x

x = 2 ( y + 6 ) +1

Reemplazamos aca

x + 6 = 3 ( 1 - 2y )

2 ( y + 6 ) +1 + 6 = 3 ( 1 - 2y )

2y + 12 + 1 + 6 = 3 - 6y

8y = 16

y = 2

 

Reemplazamos en cualquiera para sacar el valor de x

x-1 = 2 ( y + 6 )

x - 1 = 2 (8)

x = 17